Financial Literacy and Financial Inclusion for MSME Financial Behavior: The Strategic Role of E-Wallet Adoption - Uni Fardila; Bintoro Bagus Purmono; Anggraini Syahputri; M. Ridwan Ristyawan; Uray Ndaru Mustika (Journal of Educational Management Research, 2026)
This study aims to examine the effects of financial literacy and financial inclusion on e-wallet use and their implications for MSME financial behavior, while assessing the strategic role of e-wallet adoption in translating financial capabilities into financial practices. A quantitative cross-sectional survey was conducted with 210 MSME respondents selected using stratified proportional random sampling. Primary data were collected through a five-point Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. All proposed hypotheses were supported. Financial literacy (β = 0.462; t = 9.582; p < 0.001) and financial inclusion (β = 0.429; t = 8.527; p < 0.001) positively and significantly influenced e-wallet use. E-wallet use had the strongest effect on MSME financial behavior (β = 0.599; t = 12.871; p < 0.001). Financial literacy (β = 0.141) and financial inclusion (β = 0.246) also significantly affected financial behavior. The findings highlight e-wallet adoption as a strategic mechanism for translating financial capabilities into better MSME financial behavior. Therefore, financial literacy initiatives should be integrated with practical digital financial technology adoption to strengthen MSME financial management.